Snow white - N/A (Parragon books ltd, 2017)
When Snow White is taken in by the seven dwarfs, she thinks she is safe from her wicked stepmother - but she's wrong. The jealous Queen will stop at nothing to be the fairest in the land. Can the dwarfs save Snow White from the Queen's evil plan? Enjoy this exclusive large size Disney movie storybook, featuring illustrated pages fans can treasure for years to come
Keywords: English